The impact of invasive Sinanodonta woodiana (Bivalvia, Unionidae) and mussel macroparasites on the egg distribution of parasitic bitterling fish in host mussels - Halabowski, Dariusz; Pyrzanowski, Kacper; Zięba, Grzegorz; Grabowska, Joanna; Przybylski, Mirosław; Smith, Carl; Reichard, Martin (Scientific reports, 2025)
Facilitative and competitive interactions among coexisting parasite species, as well as among alternative host species, produce considerable ecological and evolutionary responses to host-parasite relationships. Such effects can be illuminated by impacts of non-native species on relationships in local communities. We used the association between parasitic European bitterling fish (Rhodeus amarus) and unionid mussels (which host bitterling eggs in their gills) to test the effects of the invasive Chinese pond mussel (Sinanodonta woodiana) and the presence of non-bitterling mussel macroparasites on the pattern of host mussel use by the bitterling across 12 unionid mussel communities with the absence or presence of S. woodiana (and variation in duration of coexistence with local species). While all six European mussel species were used by the bitterling (with the prevalence of > 30% in Unio spp.), no S. woodiana individual was infected by the bitterling. The presence of S. woodiana did not affect bitterling eggs distribution in native mussels. Large native mussels hosted more bitterling. Infection by non-bitterling parasites, mostly water mites (prevalence 47%) and trematodes (25%), did not affect rates of bitterling parasitism. We discuss our results in the context of the rapid evolution of non-native species in their new range and its implication on mussel conservation.
Keywords: Invasive species; Host-Parasite Interactions; Host selection; mlži; Ovum; zvířata; zavlečené druhy; Introduced Species; ovum; interakce hostitele a parazita; Mussel parasitism; Animals; Host-parasite interactions; Bivalvia; Freshwater mussel; Parasite facilitation